Observations and Modeling of Whistler Mode Waves in the Magnetospheric Density Ducts. Issue 10 (28th September 2020) - Streltsov, Anatoly V.; Bengtson, Miles T.
Abstract: This paper presents results from a modeling study of localized packages of very low frequency (VLF) whistler mode waves observed by the NASA Van Allen Probes (also known as the Radiation Belt Storm Probes [RBSP]) satellites in the equatorial magnetosphere. The waves are detected inside enhancements of the plasma density, which we interpret as high‐density ducts. The quality of the ducting depends on the wave and duct parameters. The goal of this study is to investigate relations between these parameters. This study is based on the analysis and simulations of the electron MHD model. The results demonstrate that (1) the high‐density ducts with the magnitudes and perpendicular sizes observed by the RBSP satellites can trap VLF waves with the observed frequency and guide them over a significant distance with little attenuation. (2) It is possible to identify the range of magnitudes of the parallel and perpendicular wavelengths using the information about frequency of the waves and parameters of the duct. Key Points: We investigate the localized packages of VLF waves detected by the RBSP‐A satellite in the equatorial magnetosphere We explain the localization of these waves by their trapping inside high‐density ducts By using the information about the duct and the wave frequency, we identify the wavelengths